Characterization of yam-growing households in the project areas of Ghana - Mignouna, Djana B.; Abdoulaye, Tahirou; Alene, A.; Asiedu, Robert; Manyong, Victor M. (2014)
The Yam Improvement for Income and Food Security in West Africa (YIIFSWA) project was initiated to assess and understand yam-based systems in order to identify the opportunities of interventions that could potentially help to increase productivity in the region. The project consists of two phases: the inception and impact study phase. During the inception phase, a baseline study was conducted in different yam-growing communities aggregated on agroecological zoning into southern Guinea savanna (SGS), derived savanna (DS), and humid forest (HF). A complementary baseline survey was commissioned in addition to the substantive data collected within the same yam belt of Ghana aiming at measuring directly yam yield from farmers’ fields in order to get more accurate crop yield estimates. The baseline studies aimed at understanding farmers’ livelihoods in yam growing areas to increase agricultural productivity in Ghana, and serve also as benchmarks to assess changes brought about by the YIIFSWA project in future. The goal of the baseline surveys was to measure the key economic and social indicators before the major components of the project implementation. Data was collected by means of structured questionnaire and a set of qualitative interview questions for focus group discussions to capture household and community specific information. The intent of the survey was to sample households within the yam belt. The survey design was based on a multistage random sampling procedure, drawing on households from yam-growing areas of Ghana; thus 600 households were selected using a sampling frame developed by extension agents in collaboration with community heads as a source list.